Peningkatan Literasi Digital Guru Sekolah Dasar melalui Pelatihan Pemanfaatan Teknologi Pembelajaran - Monica Fransisca; renny permata saputri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Digital literacy is an essential competency for elementary school teachers in responding to technological advancements and the demands of 21st-century learning. However, many elementary school teachers have not yet optimally utilized educational technology due to limited digital knowledge and skills. This community service program aims to enhance the digital literacy of elementary school teachers through training on the use of educational technology. The implementation method includes training sessions, hands-on practice, and mentoring in the use of digital learning technologies. The participants were elementary school teachers who attended the training through face-to-face sessions using a participatory approach. The results indicate an improvement in teachers’ understanding and skills in utilizing educational technology, particularly in developing simple digital learning media and digital assessment tools. This program contributes positively to improving the quality of technology-based learning in elementary schools.